Hermeneutics of Religious Freedom in Modern and Contemporary Interpretation: A Comparative Analysis between Tafsir al-Manar and Fazlur Rahman - Prisilia Maya Safa; Moh. Nor Ichwan; Auwal Salisu (Millati: Journal of Islamic Studies and Humanities, 2025)
In response to the global challenges of rising intolerance and the politicization of religion, this study explores the hermeneutics of religious freedom in Islam through a comparative analysis of Tafsir al-Manar and Fazlur Rahman’s double movement methodology. Employing a qualitative comparative design grounded in philosophical hermeneutics, the research analyzes primary texts of Tafsir al-Manar and Rahman’s key works, supported by recent secondary literature. The findings indicate that al-Manar adopts a rational-contextualist approach that prioritizes communal protection against colonial-era religious coercion, whereas Rahman articulates universal ethical principles centered on freedom of conscience, resonating with contemporary human rights discourse. This study proposes an integrative hermeneutical model that synthesizes historical consciousness with universal ethics, enabling QS. Al-Baqarah (2:256) is to be interpreted both as a safeguard against forced conversion and as a timeless affirmation of religious freedom. The proposed model offers practical implications for policy development, particularly in the areas of religious freedom advocacy, interfaith dialogue, and inclusive Islamic educational curricula. This research contributes to Qur’anic hermeneutics by bridging traditional exegesis and modern ethical concerns, offering a framework that is both contextually grounded and normatively responsive to pluralistic Muslim societies.